Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.14744/anatoljcardiol.2019.13367
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of subclinical atherosclerotic cardiovascular disease in patients with ankylosing spondylitis

Abstract: Objective: The aim of the present study was to compare patients with ankylosing spondylitis (AS) with healthy controls with respect to subclinical atherosclerotic cardiovascular disease (CVD). Methods: A total of 44 patients with AS with no history of CVD, diabetes mellitus, hypertension, chronic kidney disease, and lipid-lowering drug use were compared with 40 age-and sex-matched healthy controls with respect to carotid intima-media thickness (CIMT) and pulse wave velocity (PWV), which are surrogate markers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
3
4
0
Order By: Relevance
“…Aortic stiffness was also high in this group, suggests that an increase in stiffness is associated with the inflammatory process. 27 In our study, we found a similar relation with disease activity and strain. Aortic root strain was lower in juvenile spondyloarthropathy patients with high juvenile ankylosing spondylitis disease activity index scores.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Aortic stiffness was also high in this group, suggests that an increase in stiffness is associated with the inflammatory process. 27 In our study, we found a similar relation with disease activity and strain. Aortic root strain was lower in juvenile spondyloarthropathy patients with high juvenile ankylosing spondylitis disease activity index scores.…”
Section: Discussionsupporting
confidence: 84%
“…26 In another study, a positive relationship was found between arterial stiffness, disease activity and loss of function. 27 The authors demonstrated that erythrocyte sedimentation rate and C-reactive protein were mostly high in ankylosing spondylitis patients on conventional disease-modifying anti-rheumatic drugs. Aortic stiffness was also high in this group, suggests that an increase in stiffness is associated with the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study reported a rapid and sustained reduction of complement activation in patients with spondyloarthritis patients using TNF inhibitors and suggested that the observed decrease in cardiovascular morbidity is partly owing to its beneficial effect on complement (9). Nevertheless, the duration of the use of the TNF inhibitors was not reported in this study, and we can suggest that a multivariate analysis of the study data will confirm this protective effect of TNF therapy (1).…”
Section: Subclinical Atherosclerosis: a Hidden Threat For Patients Wimentioning
confidence: 47%
“…In the current study entitled "Assessment of subclinical atherosclerotic cardiovascular disease in patients with ankylosing spondylitis" Anatol J Cardiol 2019; 22: 185-91, Hatipsoylu et al (1), authors have failed to demonstrate the relationship between AS and atherosclerosis progression. Nevertheless, it was a study in which some main traditional risk factors for CVD were controlled.…”
Section: Subclinical Atherosclerosis: a Hidden Threat For Patients Wimentioning
confidence: 74%
“… 1 2 However, this hypothesis remains controversial in other series which have shown the absence of an increase in atherosclerosis markers in patients with SpA compared with controls. 3 4 To date, the mechanisms and mediators of accelerated atherosclerosis in SpA are not as clear as in rheumatoid arthritis. This would result from a complex interaction between the over-representation of traditional CV risk factors in patients with SpA and the inflammatory burden of the disease.…”
Section: Introductionmentioning
confidence: 99%